Investigations on the Solubility of Sn4‐Cluster Compounds in Liquid Ammonia. Issue 22 (4th September 2021) - Klein, Wilhelm; Benda, Christian B.; Henneberger, Thomas; Witzel, Benedikt J. L.; Fässler, Thomas F.
Abstract: By using different transition metal containing precursors and liquid ammonia as solvent, single crystals of Sn4 4‐ cluster containing ammoniates were grown, and three new compounds have been characterized by single crystal structure determination. K4 Sn4  ⋅ 8 NH3 (1 ) ( P 63, a =13.0370(6) Å and c =39.0889(11) Å) has been obtained by dissolving a precursor with the nominal composition "KRuSn4 " in liquid ammonia, and Rb2 Na2 Sn4  ⋅ 4.8 NH3 (2 ) ( Pc, a =9.4005(3) Å, b =15.3663(6) Å, c =12.7312(6) Å, β =94.675(3)°) from a similar solution of "Rb9 Na9 Co16 Sn24 ". 1 represents the last missing ammoniate of the A 4 Sn4 compounds with heavier alkali metal cations. K6 [OH]2 [Sn4 ] ⋅ 5 NH3 (3 ) was crystallized from solutions of the binary Zintl phase K12 Sn17 in presence of AuPPh3 Cl and cryptand[2.2.2] ( P 21 / c, a =10.3655(1) Å, b =12.7489(2) Å, c =16.9137(3) Å, β =103.212(2)°), and is the Sn4 4‐ cluster compound that appears to be stable in presence of the highest amount of hydroxide so far. Abstract :